Creative Survival in the Wasteland - David A. King (Journal of Applied Communications, 1986)
I'd like to begin this morning with a creativity drill to help us open our minds to visual thinking. Television is an emotional medium, so visualize the emotional impact of the mental images we'll be working with here.